PENGARUH INVESTASI DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Zaharani, Alwida Zia; Nasir, Muhammad (Jurnal Transformasi Administrasi, 2025)
Economic growth is a signal to achieve successful economic development in people's lives. Investment is considered as one of the factors that can increase economic growth. Economic growth and progress in a country or within a region cannot be separated from investment and controlling inflation. This research aims to determine the effect of investment in the water and sanitation sector, and inflation on economic growth in Indonesia. Water and sanitation investments were chosen because they were considered able to improve community welfare and economic productivity. Based on the Harrod-Domar theory, new investment is needed to spur economic growth, both through increasing production capacity and public spending. The type of data in this research uses time series data from 1995-2022. Data shows that Indonesia's economic growth experienced significant fluctuations during the 1995-2022 period, with an average water and sanitation investment of 17.89 USD and average inflation of 11.47 percent. The results of research using the OLS (Ordinary Least Square) model show that investment in water and sanitation has a negative and insignificant effect, while inflation has a negative and significant effect on economic growth. It is hoped that the government will maintain stability and monitor economic growth by implementing expansionary policies so that economic growth can be maintained. The government needs to maintain price stability for every product, especially basic commodities, to reduce inflation and control the amount of money circulating in society and needs to increase investment and prioritize investment in water and sanitation.